Prefrontal glutamate levels predict altered amygdala–prefrontal connectivity in traumatized youths. Issue 11 (18th September 2018) - Ousdal, Olga Therese; Milde, Anne Marita; Craven, Alexander R.; Ersland, Lars; Endestad, Tor; Melinder, Annika; Huys, Quentin J.; Hugdahl, Kenneth
Abstract: Background: Neurobiological models of stress and stress-related mental illness, including post-traumatic stress disorder, converge on the amygdala and the prefrontal cortex (PFC). While a surge of research has reported altered structural and functional connectivity between amygdala and the medial PFC following severe stress, few have addressed the underlying neurochemistry. Methods: We combined resting-state functional magnetic resonance imaging measures of amygdala connectivity with in vivo MR-spectroscopy ( 1 H-MRS) measurements of glutamate in 26 survivors from the 2011 Norwegian terror attack and 34 control subjects. Results: Traumatized youths showed altered amygdala–anterior midcingulate cortex (aMCC) and amygdala–ventromedial prefrontal cortex (vmPFC) connectivity. Moreover, the trauma survivors exhibited reduced levels of glutamate in the vmPFC which fits with the previous findings of reduced levels of Glx (glutamate + glutamine) in the aMCC (Ousdal et al ., 2017) and together suggest long-term impact of a traumatic experience on glutamatergic pathways. Importantly, local glutamatergic metabolite levels predicted the individual amygdala–aMCC and amygdala–vmPFC functional connectivity, and also mediated the observed group difference in amygdala–aMCC connectivity. Conclusions: Our findings suggest that traumatic stress may influence amygdala–prefrontal neuronal connectivity through an effect on prefrontal glutamate and its compounds. Understanding the neurochemical underpinning of altered amygdala connectivity after trauma may ultimately lead to the discovery of new pharmacological agents which can prevent or treat stress-related mental illness.